Performance Evaluate of Public Services: Study at The Government and Borders Bureau of Kepulauan Riau Province - Indra Bastian Tahir (Badan Perencanaan, Penelitian dan Pengembangan Pemerintah Provinsi Kepulauan Riau, 2022)
Performance evaluate of public services is one of the processes leading to improve public services so that development goals can be immediately achieved, that is the creation of general welfare. The purpose of this study was to analysis the performance of public services in Government and Border Bureau Setda Province Kepulauan Riau. The study uses descriptive qualitative with Likert scale which provides an overview of the phenomena that occur in the field and presents data in a systematic, factual, and accurate manner from service recipients. The data collection techniques used in the study by surveying through online questionnaires. The elements surveyed are 1) Service Requirements, 2) Service Systems, Mechanisms and Procedures, 3) Service Time, 4) Product Specifications & Service Fees/ Tariffs, 5) Implementing Competencies & Behaviors, 6) Service Facilities and Infrastructure, and 7) Website Info and Complaint Handling, Suggestions & Feedback. In general the results show that the performanceof public services at the Government and Border Bureau is seen in terms of work quality by assessing the service results felt by service recipients that are XX, included in category B with good service performance as expected.